2014
DOI: 10.1038/jhg.2014.96
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of genetic factors underlying typical orofacial clefts: mutational screening and copy number variation

Abstract: Typical orofacial clefts (OFCs) comprise cleft lip, cleft palate and cleft lip and palate. The complex etiology has been postulated to involve chromosome rearrangements, gene mutations and environmental factors. A group of genes including IRF6, FOXE1, GLI2, MSX2, SKI, SATB2, MSX1 and FGF has been implicated in the etiology of OFCs. Recently, the role of the copy number variations (CNVs) has been studied in genetic defects and diseases. CNVs act by modifying gene expression, disrupting gene sequence or altering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 63 publications
0
30
0
5
Order By: Relevance
“…Among the 39 genes analyzed, 16 were associated with NSCLP, including two novel genes, TCEB3 and KIF7, both of which were recently proposed (Simioni et al, 2015). Interestingly, stepwise regression analysis revealed that 15.5% of the NSCLP etiology could be explained by 11 genes: The present study is the first to report association of TCEB3…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
See 3 more Smart Citations
“…Among the 39 genes analyzed, 16 were associated with NSCLP, including two novel genes, TCEB3 and KIF7, both of which were recently proposed (Simioni et al, 2015). Interestingly, stepwise regression analysis revealed that 15.5% of the NSCLP etiology could be explained by 11 genes: The present study is the first to report association of TCEB3…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
“…This potential association was initially reported based on a copy number study in CL/P individuals (Simioni et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Ран-ние стадии одонтогенеза регулируют, в частности, такие сигнальные молекулы, как: PAX9, MSX1, фактор роста нервов (nerve growth factor, NGF), костный морфогенети-ческий белок (bone morphogenetic protein, BMP), фактор роста фибробластов (fibroblast growth actor, FGF), продук-ты генов семейства Hedgehog (Sonic Hedgehog, SHH), Distal-less (DLX) и Wingless (WNT). Доказано, что мутации генов MSX1 и PAX9 приводят к селективной аплазии зу-бов [4,6,33,44,46,47], при этом мутации MSX1 также отвечают за развитие некоторых расщелин лица [30,35].…”
unclassified